Pengaruh Dukungan Organisasi terhadap Keinginan Keluar Karyawan dengan Keterikatan Kerja sebagai Variabel Mediasi (Studi pada Karyawan tetap PT. X) - Pratama, Daffa Ikhlasul; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT The company must retain high-quality employees to reduce voluntary turnover amid the current complexity of the industry. Work Engagement (WE) and Perceived Organizational Support (POS) play crucial roles in diminishing employees' inclination to leave. Strengthening work engagement and enhancing employees' perception of organizational support can help create a positive work environment, boost productivity, and build the company's reputation. This research adopts a quantitative approach using Factor Analysis and Structural Equation Model (SEM) with SmartPLS 3 and SPSS 25. Results indicate that when employees feel supported by the company, their desire to leave diminishes. Additionally, the study shows a positive correlation between work engagement and organizational support, leading to a lower likelihood of employees leaving the company. PT. X can conduct evaluations through surveys and counseling to better understand employees' needs. Actions such as recognition, open communication, work-related information sharing, and offering career development programs can further enhance employee engagement